Study on Mechanical Properties of PET Fiber-Reinforced Coal Gangue Fine Aggregate Concrete - Yanlin Huang; An Zhou (Geofluids)
In recent years, with the rapid development of the construction industry, the demand for natural river sand has become increasingly prominent. Development of alternatives to river sand has become an interesting direction for concrete research. In this paper, coal gangue was proposed to replace part of the river sand to produce coal gangue fine aggregate concrete, while waste polyethene terephthalate (PET) bottles were used as raw materials to make PET fibers to improve the mechanical properties of coal gangue fine aggregate concrete. There were two parts of the test conducted. In the first part, the compressive strength of the gangue fine aggregate concrete cube, splitting tensile strength, axial compressive strength, and static elastic modulus were studied when the substitution rate of coal gangue increased from 0% to 50%. Referring to the equation of the full stress-strain curve of plain concrete, the stress-strain constitutive equation of coal gangue fine aggregate concrete was analyzed and studied. By comparing with plain concrete, it was found that the coal gangue concrete with a replacement rate of 50% had higher compressive strength and tensile strength, but its brittleness was significantly greater than that of plain concrete in the later stage. In the second part, by studying the effect of different PET fiber content on the mechanical properties of coal gangue fine aggregate concrete with a replacement rate of 50%, it was found that when the addition of PET fiber was 0.1% and 0.3%, not only were compressive strength, splitting tensile strength, static elastic modulus, and flexural strength of the gangue fine aggregate concrete effectively improved but also the brittleness of concrete can be significantly reduced. The study found that after adding 0.3% PET fiber, the coal gangue fine aggregate concrete with a replacement rate of 50% has better mechanical properties and less brittleness.